Perceived organizational support towards affective organizational commitment among workers’ in Syarikat Air Melaka Berhad (SAMB) / Nurulain Hamali - Hamali, Nurulain (2009)
The main objective of this paper is to examine the relationships between perceived organizational support (POS) and affective organizational commitment of workers’ working for Syarikat Air Melaka Berhad (SAMB) in Malacca. Also to determine the extent to which perceived organizational support influenced commitment of SAMB’s workers to that organization, to reduce turnover intent and quality of service rendered. This study also using sample size of 133 respondents and choose non-probability as sampling technique. Furthermore, this studies also using primary and secondary data. Findings are interpreted using frequency and percent, descriptive statistics and also correlation. Finally, there are some conclusions and some recommendations for future research.